MAXIMUM POWER POINT TRACKER USING GENETIC FUZZY CONTROLLER FOR PHOTOVOLTAIC GRID CONNECTED ARRAY - TKOUTI, N.; MOUSSI, A. (Courrier du Savoir, 2015)
ABSTRACT paper presents a fuzzy logic controller (FLC) used as a maximum power point tracker(MPPT) of a line commutated inverter in a photovoltaic (PV) grid connected system, under variable irradiance conditions. The purpose is to find the relationship between the maximum power point (MPP) and weather parameters and track the MPP and transferring the maximum power to utility grid. The design of control rules were found by genetic algorithms (GAs) to modulate the firing angle of the inverter for tracking the MPP. Simulation results prove the superior tracking efficiency of the fuzzy controller optimized under variable parameters. KEYWORDS: Fuzzy Controller, Genetic Algorithm, Grid Connection, Maximum Power Point Tracking, Photovoltaic Energy. Weather conditions.